The oral-gut microbiota relationship in healthy humans: identifying shared bacteria between environments and age groups - Costa, Carolina F. F. A.; Correia-de-Sá, Teresa; Araujo, Ricardo; Barbosa, Fernando; Burnet, Philip W. J.; Ferreira-Gomes, Joana; Sampaio-Maia, Benedita (Frontiers in Microbiology, 2024)
Although the oral cavity and the gut are anatomically continuous regions of the gastrointestinal tract, research on the relationship between oral and gut microbiota remains sparse. Oral-gut bacterial translocation is mostly studied in pathological contexts, thus evidence of translocation in healthy conditions is still scarce. Studying the oral-gut microbiota relationship in humans in different life stages is necessary in order to understand how these microbial communities might relate throughout life.In this study, saliva and faecal samples were collected from healthy participants (39 children, 97 adults). Microbiota analysis was carried out by sequencing the V4 region of the 16S ribosomal RNA gene, followed by amplicon sequence variant (ASV) analysis.Although the oral and gut microbiota are vastly different, a subset of 61 ASVs were present in both the oral cavity and gut of the same individual, and represented 1.6% of all ASVs detected. From these, 26 ASVs (classified into 18 genera: